Aerobic exercise training in the treatment of non‐alcoholic fatty liver disease related fibrosis. (27th May 2016) - Linden, Melissa A.; Sheldon, Ryan D.; Meers, Grace M.; Ortinau, Laura C.; Morris, E. Matthew; Booth, Frank W.; Kanaley, Jill A.; Vieira‐Potter, Victoria J.; Sowers, James R.; Ibdah, Jamal A.; Thyfault, John P.; Laughlin, M. Harold; et al.
Abstract : Key points: Physiologically relevant rodent models of non‐alcoholic steatohepatitis (NASH) that resemble the human condition are limited. Exercise training and energy restriction are first‐line recommendations for the treatment of NASH. Hyperphagic Otsuka Long–Evans Tokushima fatty rats fed a western diet high in fat, sucrose and cholesterol for 24 weeks developed a severe NASH with fibrosis phenotype. Moderate intensity exercise training and modest energy restriction provided some improvement in the histological features of NASH that coincided with alterations in markers of hepatic stellate cell activation and extracellular matrix remodelling. The present study highlights the importance of lifestyle modification, including exercise training and energy restriction, in the regulation of advanced liver disease. Abstract: The incidence of non‐alcoholic steatohepatitis (NASH) is rising but the efficacy of lifestyle modifications to improve NASH‐related outcomes remain unclear. We hypothesized that a western diet (WD) would induce NASH in the Otsuka Long–Evans Tokushima Fatty (OLETF) rat and that lifestyle modification would improve this condition. Eight‐week‐old Long–Evans Tokushima Otsuka (L) and OLETF (O) rats consumed a control diet (10% kcal fat, 3.5% sucrose) or a WD (45% kcal fat, 17% sucrose, 1% cholesterol) for 24 weeks. At 20 weeks of age, additional WD‐fed OLETFs were randomized to sedentary (O‐SED), food restriction (O‐FR; ∼25% kcal reduction vs . O‐SED) or exercise training (O‐EX; treadmill running 20 m min –1 with a 15% incline, 60 min day –1, 5 days week –1 ) conditions for 12 weeks. WD induced a NASH phenotype in OLETFs characterized by hepatic fibrosis (collagen 1α1 mRNA and hydroxyproline content), as well as elevated inflammation and non‐alcoholic fatty liver disease activity scores, and hepatic stellate cell activation (α‐smooth muscle actin) compared to Long–Evans Tokushima Otsuka rats. FR and EX modestly improved NASH‐related fibrosis markers (FR: hydroxyproline content, P <  0.01; EX: collagen 1α1 mRNA, P <  0.05; both: fibrosis score, P <  0.01) and inflammation (both: inflammation score; FR: interleukin‐1β and tumor necrosis factor α) vs . O‐SED. FR reduced hepatic stellate cell activation markers (transforming growth factor‐β protein and α‐smooth muscle actin mRNA), whereas EX increased the hepatic stellate cell senescence marker CCN1 ( P <  0.01  vs . O‐SED). Additionally, both FR and EX normalized extracellular matrix remodelling markers to levels similar to L‐WD ( P  > 0.05). Although neither EX nor FR led to complete resolution of the WD‐induced NASH phenotype, both independently benefitted liver fibrosis via altered hepatic stellate cell activation and extracellular matrix remodelling. Key points: Physiologically relevant rodent models of non‐alcoholic steatohepatitis (NASH) that resemble the human condition are limited. Exercise training and energy restriction are first‐line recommendations for the treatment of NASH. Hyperphagic Otsuka Long–Evans Tokushima fatty rats fed a western diet high in fat, sucrose and cholesterol for 24 weeks developed a severe NASH with fibrosis phenotype. Moderate intensity exercise training and modest energy restriction provided some improvement in the histological features of NASH that coincided with alterations in markers of hepatic stellate cell activation and extracellular matrix remodelling. The present study highlights the importance of lifestyle modification, including exercise training and energy restriction, in the regulation of advanced liver disease.